Analisa Kecukupan Penerapan Pengawasan Internal Dengan Metode System Development Life Cycle PT. XYZ - Martias, Andi (Universitas Bina Sarana Informatika, 2018)
Abstract In order to improve the efficiency of operational activities and the quality of the Company's services to its customers, the Company is required to develop the Company's business strategy, among others, by utilizing the progress of Information Technology (IT). The development of these strategies further encourages new investments in IT used in transaction processing and information. The Company's reliability of managing IT determines success in generating a complete, accurate, current, complete, secure, consistent, timely and relevant information. As a growing company is required to develop other business strategies by utilizing information technology in providing services to its customers. Therefore PT XYZ Application SDLC (System Development Life Cicle) with SDLC resolution is System Development Life Cycle (SDLC), is a method of developing / designing computer-based application system that guide the steps to build the system. User Requirement, System Design, System Development, System Testing, User Acceptance Test, System Deployment, Post Implementation Review and Disposa System. Internal auditing is an independent party typically used within an organizational structure but can not be part of a team member who serves to provide input in confirmation of the adequacy of the control (advisory capacity). Based on the conclusion, the author uses several things to know 1) physical security performance against spreading room, 2) optimal performance of SDLC, 3) increasing understanding of dual custody password. It is expected to improve the quality control of the company's internal processes and protect the company's data. Keywords: Internal Control. System Development Life Cycle